Upoštevanje razvoja vrednot pri spodbujanju čistega športa - Kajtna, Tanja (Šport (Ljubljana), 2020)
The article presents a method for promoting fair engagement in sport and compliance with the rules in sport for young people who are just starting to learn about sport through their personal values. At the beginning, some definitions of values are provided and development of values during an individual's life is presented in accordance with the definition by Musek (2000) which was based on the results of his study. We will present an example as a tool to influence development of values by encouraging critical thought about the values in sport. It is particularly important that the materials used are suitable for children. We will present two booklets where the behaviour of an imaginary character is used to promote the values we want to see in adult athletes and people in general. The booklets are unique on a global scale.
Keywords: development of values; doping; literarni motivi; literary motives; moral development; moralni razvoj; razvoj vrednot; šport; values; vrednote